Systematic Literature Review (SLR): Evaluation of the Sustainable Public Space’s Indicators - Monica Sheira; Susilo Kusdiwanggo (Jurnal Lingkungan Binaan Indonesia, 2026)
Growing discussions on public space highlight the need for a more structured understanding of sustainability indicators across diverse urban contexts. This study examines these indicators across 22 selected articles using a Systematic Literature Review (SLR) and then tests them through an empirical example of the Prawirotaman Street corridor in Yogyakarta to observe how the theoretical concepts operate in practice. The analysis integrates SLR findings with primary data such as field observations and interviews to assess the degree of indicator fulfilment in real public-space conditions. The study offers a comprehensive indicator model and demonstrates its partial applicability in the local context, providing a novel evaluative framework for future public space assessments in Indonesia.